Does Duration of Pain at Baseline Influence Longer-term Clinical Outcomes of Low Back Pain Patients Managed on an Evidence-Based Pathway?. Issue 3 (1st February 2021) - Jess, Mary-Anne; Ryan, Cormac; Hamilton, Sharon; Wellburn, Shaun; Atkinson, Greg; Greenough, Charles; Peat, Glynis; Coxon, Andrew; Fatoye, Francis; Ferguson, Diarmaid; Dickson, Alastair; Ridley, Helen; et al.
Abstract : Study Design: Nonrandomized longitudinal observational study. Objective: The aim of this study was to evaluate the association between baseline pain duration and medium-to-long term clinical outcomes, in low back pain (LBP) patients enrolled on the North East of England Regional Back Pain and Radicular Pain Pathway (NERBPP). Summary of Background Data: The NERBPP is based upon National Institute for Health and Care Excellence (NICE) guidelines. These guidelines no longer differentiate management of LBP patients based on pain duration. Medium-to-long term data from the NERBPP is lacking. Methods: Between May 2015 and December 2019, 786 and 552 LBP patients from the NERBPP returned 6-month and 12-month follow-up outcome measures, respectively. Outcomes included pain (Numerical rating scale), function (Oswestry Disability Index) and quality-of-life (EuroQol five-dimension, five-level questionnaire), analyzed using a series of covariate-adjusted models. Patients were categorized into four groups based upon baseline pain duration: <3 months, ≥3 to <6 months, ≥6 months to <12 months, ≥12 months. Results: Patients with <3 months duration demonstrated clinically important improvements on all outcomes, at both follow-ups. The improvements in outcomes from this group were larger than those in the ≥12 month's duration group ( P < 0.05), these group differences in change, in some cases surpassed our threshold for clinical relevance. Functional improvements in those with ≥12 month's duration were not clinically relevant at either follow-up. All patients, regardless of baseline pain duration, reported similar levels of readiness to self-manage at the 12-month follow-up. Conclusion: Baseline pain duration would appear to be of clinical importance. Patients with shorter baseline pain duration demonstrated better outcomes. Those with ≥12 month's duration of pain may need additional support during their management to achieve clinically relevant functional improvements in the medium-to-long term. These findings raise questions about the decision by NICE to move away from duration of pain to differentiate management of LBP patients. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the textFollowing management on the North East of England Regional Back Pain and Radicular Pain Pathway patients with shorter baseline duration of low back pain (LBP) demonstrated clinically important improvements on a suite of clinical outcome measures compared to those with ≥12 month's duration of LBP. The latter may need additional support to achieve clinically relevant functional improvements in the medium-to-long term.